Effect of Turning Parameters on Surface Roughness of Aluminum Casting Semi-Solid - Ratanawilai, Thanate (RESEARCH AND DEVELOPMENT JOURNAL, 2013)
To study the effect of turning parameters on surface roughness of aluminum casting semi-solid, the experiment was conducted on a computer numerical control machine using carbide insert (Plansee Tizit; DCGT 070204FN-27 grade H10T Co 6.0%) as a cutting tool. The 3 cutting factors were studied including cutting speed, feed and depth of cut in the range of 130-220 m./min, 0.02-0.1 mm./rev and 0.45- 0.85 mm., respectively. The results showed that feed rate was the most affected factor to the finish surface roughness. Decreasing the feed rate gave the better surface roughness. Finally, the regression equation was validated by comparing the value of surface roughness from the equation and the actual experiment. It was found that the absolute different value was approximately 4.22% which is in the range of acceptable criteria.